Agriculture gets recognised at COP17 in Durban - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
Despite the fact that agriculture both is a driver and victim of climate change, the sector was sidelined in the United Nations Framework Convention on Climate Change (UNFCCC) negotiations in 2009 and 2010. A breakthrough occurred in 2011, at COP17 in Durban, when agriculture was referred to the Subsidiary Body for Scientific and Technological Advice (SBSTA) agenda for more detailed discussion. CCAFS, in collaboration with many other agencies, helped achieve this groundbreaking outcome. Notably, the Meridian Institute convened a group of independent experts and negotiators to develop an objective report on key issues and policy options in relation to agriculture and climate change.